Transfusion effects on cardiomyocyte growth and proliferation in fetal sheep following chronic anemia - Jonker, Sonnet S. (2011)
Chronic fetal anemia results in significant cardiac remodeling. The capacity to reverse these effects is unknown. We examined the effects of transfusion on cardiomyocyte adaptations following chronic anemia in fetal sheep subjected to daily hemorrhage beginning at 109d gestation age (GA; term ∼145d). Following 10 days of anemia, one group was euthanized for comparison to age-matched controls. A separate group of anemic fetuses was transfused with red blood cells at 119d GA for comparison to controls at 129d GA. Anemia significantly increased the heart-to-body weight ratio, an effect partially ameliorated following transfusion. Cardiomyocyte dimensions were similar among all groups, suggesting an absence of hypertrophy. The percentages of mono- and binucleated cardiomyocytes were similar between groups at 119d GA, though the percentage of binucleated cells was significantly less in transfused fetuses compared to controls at 129d GA. Protein levels of mitogen activated protein kinases and protein kinase B were similar between controls and their respective intervention groups, except for a significant increase in phosphorylated c-Jun N-terminal kinase 1/2 (JNK1/2) in transfused fetuses. Thus, cardiomyocyte proliferation but not hypertrophy contributes to cardiac enlargement during fetal anemia. Transfusion results in slowing but not cessation of cardiac growth following anemia.